Identification and Analysis of Circular RNAs in Mammary Gland from Yaks Between Lactation and Dry Period - Yilin Shi; Xiaoyun Wu; Guangyao Meng; Xiaoming Ma; Yongfu La; Pengjia Bao; Min Chu; Ping Yan (Animals)
Lactation is a complex physiological process regulated by numerous genes and factors. Circular RNA (circRNA), a non-coding RNA, acts as a molecular sponge that sequesters microRNAs (miRNAs) to regulate target gene expression. Although circRNA has been linked to mammary gland lactation, its specific role in yaks remains underexplored. This study employed circular RNA sequencing (circRNA-seq) to examine the differential expression of circRNAs in yak mammary tissues during lactation and the dry period. Additionally, an enrichment analysis of the differentially expressed circRNAs (DECs) was performed. A competing endogenous RNA (ceRNA) network was then constructed to explore the potential of their roles in lactation and mammary gland development. We detected 18,905 circRNAs in yak mammary tissue, among which 302 showed differential expression. The host genes of these DECs were enriched in functions and pathways associated with yak milk synthesis and composition. Through the construction of a ceRNA network and the enrichment analysis of associated mRNAs, this study identified ceRNAs potentially involved in regulating lactation and mammary gland development. In conclusion, circRNAs in yak mammary tissues were identified and analyzed across lactation and dry periods, establishing a ceRNA network related to lactation regulation. These findings provide novel insights into the regulatory mechanisms governing lactation in yaks (Bos grunniens).